2016
DOI: 10.1016/s0140-6736(16)30580-3
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for prevention of delirium in elderly patients after non-cardiac surgery: a randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackground Delirium is a postoperative complication that occurs frequently in patients older than 65 years, and presages adverse outcomes. We investigated whether prophylactic low-dose dexmedetomidine, a highly selective α 2 adrenoceptor agonist, could safely decrease the incidence of delirium in elderly patients after non-cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
577
10
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 629 publications
(666 citation statements)
references
References 52 publications
31
577
10
13
Order By: Relevance
“…These investigators found that only a small proportion of dexmedetomidine studies investigated its effect on delirium, reflecting a potentially lower quality of evidence influenced by risk of bias, imprecision, and significant publication bias. However, further trials favoring dexmedetomidine were published since this meta‐analysis62 and a recent meta‐analysis comparing dexmedetomidine to propofol in post‐cardiac surgery patients that included 8 randomized trials demonstrated that dexmedetomidine was associated with a lower risk of delirium (risk ratio, 0.4; 95% CI, 0.24–0.64; P =0.0002) as well as shorter length of intubation, but more bradycardia 68…”
Section: Preventionmentioning
confidence: 98%
“…These investigators found that only a small proportion of dexmedetomidine studies investigated its effect on delirium, reflecting a potentially lower quality of evidence influenced by risk of bias, imprecision, and significant publication bias. However, further trials favoring dexmedetomidine were published since this meta‐analysis62 and a recent meta‐analysis comparing dexmedetomidine to propofol in post‐cardiac surgery patients that included 8 randomized trials demonstrated that dexmedetomidine was associated with a lower risk of delirium (risk ratio, 0.4; 95% CI, 0.24–0.64; P =0.0002) as well as shorter length of intubation, but more bradycardia 68…”
Section: Preventionmentioning
confidence: 98%
“…A multicentre study on that strategy has just been completed and is awaiting final analyses [22]. Experiences from perioperative care in VOPs also suggest that preoperative prophylaxis with haloperiodol [23] and recently with dexmedetomidine [24] also may be effective.…”
Section: Deliriummentioning
confidence: 99%
“…Dexmedetomidine for prevention of delirium in elderly patients after non-cardiac surgery those that are not intubated, reduces the risk of delirium in the postoperative period (26).…”
Section: Commentarymentioning
confidence: 99%